(untitled) (INNOVATIVE ECONOMY, 2020)
Zhukovska A.Yu. INNOVATIVE TECHNOLOGIES OF INCLUSIVE MEDICINE Purpose. The aim of the article is to substantiate the innovative technologies of inclusive medicine, in particular the analysis of the state of development of telemedicine in Ukraine and the substantiation of the prospects of its development. Methodology of research. The theoretical and methodological basis of the study are the fundamental provisions of modern economic theory, scientific works of leading foreign and domestic scientists, international and domestic normative and legal regulations on health care. General and special research methods are used to achieve this goal, in particular: the method of system analysis – for the study of telemedicine as a system; method of structural analysis – to study the model of telemedicine; method of comparison – to compare different definitions of “telemedicine”. Findings. The necessity of using an inclusive approach in medicine is substantiated. The author’s definition of the concept of “inclusive medicine” is offered. The forecast of development of the world market of e-medicine is analysed and it is defined that the perspective direction of development of e-medicine is telemedicine. The definitions of “telemedicine” are analysed and grouped into: definitions that treat telemedicine as a field of medicine, and definitions that treat telemedicine as a way of providing medical services, and on this basis, the author’s definition of “telemedicine” is proposed. The state of development of telemedicine in Ukraine is studied and the prospects of its development are substantiated. The benefits of the development of telemedicine for patients, for health professionals, for health care facilities and the health care system in general are substantiated. Originality. For the first time, it is proposed to define the concept of “inclusive medicine” as a comprehensive process of ensuring equal timely access to quality medical services for all persons, regardless of their health, location, nationality, religion, etc. Practical value. Substantiated priorities for the further development of domestic telemedicine can be used in the development of strategic guidelines for the development of the health care system. Key words: inclusion, healthcare, e-medicine, telemedicine, inclusive medicine, innovative technologies.